Civil-military relations, coup-proofing, and militaries in the Arab Spring - Al-Hamdi, Mohaned Talib (Kansas State University, 2020)
In late 2010 and early 2011, some Arab countries witnessed mass protests that led to different outcomes. These protests are considered a turning point in the contemporary history of the Middle East and North Africa (MENA) region. The protests were a natural outcome of the social, political, and economic conditions that the Arab population had been enduring under the totalitarian regimes who could not understand and deal with the changing circumstances in their countries. The goals of the protests were to improve the living conditions of the population and empower the youth, women, and the marginalized. The term coined to describe these protests was the “Arab Spring” revolutions. Often in history, when protesters have threatened a regime, political leaders have tried to suppress them by using force. Before the Arab Spring, most literature on civil-military relations in the MENA region assumed that the Arab armies represented homogeneous entities whose interests aligned with the interests of the leaders of the states. Some scholars went further to attribute the stability of authoritarian regimes for long periods in the Middle East to the support of these security services. This study is a systematic examination of the civil-military relations in the Arab World during the time of change. It argues that historical evolution of civil-military relations during state-formation periods and the formation of armed forces along ethnic, religious, and tribal lines in the Arab majority countries are significantly related to the outcomes of uprisings. My hypothesis is that Arab militaries’ actions during the uprisings and the resulting outcomes, whether civil war, democratization, or authoritarianism were products of decades of different and dissimilar ways that the civil-military relations and the states developed in those countries. Social and ethnic configuration of the armed forces also played an important role in shaping the protest outcomes. The objective of this study is to explain the different responses and reactions of the armed forces to the popular uprisings in those Arab countries. I explain why the behavior of each country’s military differed during the Arab Spring revolutions in Egypt, Libya, Yemen, Tunisia, and Syria using comparative case study method. I use these cases to both develop a theory about different outcomes of the uprisings and test the implications of this theory. For robustness check, I apply my theoretical framework to the new wave of the uprisings unfolding in Algeria, Sudan, Lebanon, and Iraq. By and large, the evidence supports my explanation about the roles of historical development of civil-military relations and social composition of armed forces in shaping the outcomes of mass protests.
Keywords: Civil-Military Realtions; Coup-Proofing; Arab Militaries; Arab Spring